2021
DOI: 10.3389/fimmu.2021.666223
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Circulatory Cytokines and Chemokines in Human Coronaviruses: A Systematic Review and Meta-Analysis

Abstract: BackgroundSARS, MERS, and COVID-19 share similar characteristics. For instance, the genetic homology of SARS-CoV-2 compared to SARS-CoV and MERS-CoV is 80% and 50%, respectively, which may cause similar clinical features. Moreover, uncontrolled release of proinflammatory mediators (also called a cytokine storm) by activated immune cells in SARS, MERS, and COVID-19 patients leads to severe phenotype development.AimThis systematic review and meta-analysis aimed to evaluate the inflammatory cytokine profile assoc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 123 publications
0
24
1
2
Order By: Relevance
“…Although not statistically significant, we observed that the IL6 level on the 14th day was below that of the cases that did not take vitamin D supplements. A systematic review and meta-analysis study reported that elevated IL6 levels are associated with COVID-19 severity [48]. In the study of Li et al, COVID-19 patients had higher IL6 mRNA expression levels compared with healthy individuals [47].…”
Section: Vitamin D and Covid-19mentioning
confidence: 99%
“…Although not statistically significant, we observed that the IL6 level on the 14th day was below that of the cases that did not take vitamin D supplements. A systematic review and meta-analysis study reported that elevated IL6 levels are associated with COVID-19 severity [48]. In the study of Li et al, COVID-19 patients had higher IL6 mRNA expression levels compared with healthy individuals [47].…”
Section: Vitamin D and Covid-19mentioning
confidence: 99%
“…Besides, impaired Type-I IFN responses to SARS-CoV-2 in the initial stage may lead to a cytokine storm (7). Several previous studies, including a systemic review and meta-analysis, revealed that the occurrence of cytokine storm is associated with COVID-19 severity and mortality (3,4,(7)(8)(9)(10). Therefore, early identification and optimal treatment of cytokine storms are pivotal in improving disease outcomes (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Surgical masks and N95 respirators are recommended for healthcare workers [ 12 ]. While previous studies in Saudi Arabia have focused on the clinical and mental consequences of COVID-19 [ 13 , 14 , 15 , 16 , 17 ], very few studies have explored community knowledge and attitudes towards the disease, and most of them are restricted to a specific governorate or area. Therefore, this study aimed to assess the community knowledge of and to obtain a broad overview of attitudes towards the appropriate prevention techniques that are recommended by the Ministry of Health (MOH) to prevent COVID-19 transmission in Saudi Arabia before the emergence of COVID-19 drift variants.…”
Section: Introductionmentioning
confidence: 99%